(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article is devoted to the methodological possibilities and content of studying adaptation and emotional stress. The text of the article also covers in detail issues such as the study of the adaptation process and emotional stress, assessing the level of adaptation of a person to the environment, determining the ability to manage stress, and measures of psychological support.